Optimizing FPSH-HAM in Fostering Leadership Character with Integrity at SMAN 1 Batujajar, West Bandung Regency - Regina Dalih Gandes Ivoni Lubis; Jajang Hendar Hendrawan; Neneng Tripuspita (STKIP Taman Siswa Bima, 2025)
This study aims to examine the optimization of the Student Forum for Law and Human Rights Awareness (FPSH-HAM) as a strategic platform in fostering integrity-based leadership character at SMAN 1 Batujajar. The research is motivated by growing concerns over the decline in legal awareness and moral degradation among youth, which often leads to deviant behaviors. FPSH-HAM serves as a non-formal educational initiative that integrates the values of law, human rights, and leadership integrity. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation. The results reveal that active student participation, support from school stakeholders, and ongoing leadership development programs have significantly contributed to shaping responsible, disciplined, and law-conscious student leaders. FPSH-HAM has proven to be effective in internalizing character values and encouraging students to become change agents in their schools and communities. These findings underscore the importance of strengthening youth organizations rooted in law and human rights education as a foundation for building an excellent future generation.